Evaluation of Financial Performance : Case Study at the Population and Civil Registration Service Wondama Bay Regency - Yohanis Silfester Lefteuw; Adriansyah (Medikun Publisher, 2024)
This research is based on the importance of evaluating financial performance as a step to improve the efficiency and effectiveness of budget use at the Department of Population and Civil Registration. The aim is to evaluate and analyze financial performance, including budget allocation, fund usage efficiency, and compliance with financial regulations. The method used is descriptive quantitative analysis by utilizing financial data from previous years and conducting in-depth interviews with related staff to gain further insights into budget implementation. The research results indicate several weaknesses in the financial management system that impact the achievement of department performance targets, such as misalignment of budget allocation with activity priorities and delays in budget realization processes. The implications are the need for improvements in the internal control system and enhancement of the capacity of human resources involved in financial management, with the hope of helping the Department of Population and Civil Registration improve financial performance